Pengembangan e-LKPD Berbasis Problem Based Learning Pada Materi Hukum-hukum Dasar Kimia - Indah Monica; Nurhamidah; elvinawati (University of Bengkulu, 2023)
This study aims to determine the feasibility and response of students to the e-LKPD based on Problem Based Learning (PBL) on the materials on the basic chemical laws that were developed. The development model used is the 4-D model (Define, Design, Develop and Disseminate) which was limited to the develop-stage. The research subjects were 27 students from class XI MIPA 2 at SMA Negeri 03 Bengkulu Tengah for the 2022/2023 academic year. The research was from January to September 2022. The instruments in this study were interview sheets, observation sheet, student needs questionnaires, validation sheets and student response questionnaires. The data generated was in the form of qualitative data in the form of suggestions from the validator as well as quantitative data resulting from validation sheets and student response questionnaires. From the research results obtained (1) the Problem Based Learning-based e-LKPD developed was stated to be very feasible by material experts with a percentage of 88% where the lowest score was in the linguistic aspect, while media experts also stated it was very feasible with a percentage of 93.5% where the score the lowest is in the graphical aspect, (2) the results of student responses to the e-LKPD Problem Based Learning are in the very good category with a percentage of 84.76% where the lowest score is in the aspect of ease of understanding. The conclusion based on the results of the validation and student responses shows that the Problem Based Learning-based e-LKPD that has been developed is very feasible for use in the learning process on material basic chemical laws.